Degradation of 2-chlorophenol in dielectric barrier discharge reactor. Issue 1 (January 2021) - Suryo, Samantha; Diristiani, Febri Monica; Khairunizzahrah, Badzlina; Bismo, Setijo
Abstract: Liquid waste containing 2-chlorophenol compound has high toxicity, carcinogenic, and poor degradation properties, leading to bioaccumulation in the environment. It also considered as a primary chemical feedstock in the manufacture and widely used in various industry. Conventional methods such as chlorination, adsorption, liquid-liquid extraction, steam distillation, photocatalytic are inefficient and expensive. Plasma technology with a non-thermal dielectric barrier discharge (DBD) plasma reactor can efficiently degrade chlorophenol compounds without producing side effects. Various active species produced in the reactor are electrons and radical compounds OH, O3, H2 O2 . This study aims to evaluate the degradation performance of DBD plasma reactors, namely the percentage of degradation, degradation concentrations of 2-chlorophenol, and chemical oxygen demand (COD). Variations were made with pH 4 and 10, while the fixed variables were waste flow rate 50 mL/min, air flow rate 2.5 L/min, and plasmatron voltage 19kV. It was found that degradation process of 2-chlorophenol with DBD reactor in pH 4 and 10 achieve 70.96% and 79.41%, respectively.